1984
DOI: 10.1128/jb.159.2.618-623.1984
|View full text |Cite
|
Sign up to set email alerts
|

Location and analysis of nucleotide sequences at one end of a putative lac transposon in the Escherichia coli chromosome

Abstract: A segment of Escherichia coli DNA that contained a discontinuity of homology with Salmonella typhimurium DNA was isolated. The segment, 1,430 base pairs long, was derived from one end of the lac "loop," a region of about 12 kilobase pairs of E. coli DNA, including the lac operon which has no detectable homology with S. typhimurium DNA (K. Lampel and M. Riley, Mol. Gen. Genet. 186:82-86, 1982). The nucleotide sequence of the 1,430-base-pair segment of DNA was determined. The location of the junction of disconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…IC and the sequence of one strand is given in Fig, 2. A computer search revealed that the 1426 bp Pst\-Pvu\\ fragment present on pSD112 (open bar in Fig, 1C) had previously been sequenced by Buvinger et al (1984) in a study of the discontinuity of homology with S, typhimurium DNA.…”
Section: Nucleotide Sequence Of the Coda Regionmentioning
confidence: 99%
“…IC and the sequence of one strand is given in Fig, 2. A computer search revealed that the 1426 bp Pst\-Pvu\\ fragment present on pSD112 (open bar in Fig, 1C) had previously been sequenced by Buvinger et al (1984) in a study of the discontinuity of homology with S, typhimurium DNA.…”
Section: Nucleotide Sequence Of the Coda Regionmentioning
confidence: 99%
“…In addition, small insertions or deletions distinguish the linkage maps of E. coli and S. typhimurium (15,33,34). For example, E. coli ferments lactose, while S. typhimurium is Lac-; loops of DNA which carry several genes, including lac, are present in E. coli but missing from S. typhimurium (7,16). More data are needed to clarify the relative roles of sequence divergence in homologous genes and chromosomal rearrangements in the evolution of different genera.…”
mentioning
confidence: 99%
“…These events are reasonably described by recA-dependent recombination between pairs of insertion elements.There are features of the proA-purE region of the chromosome that are not explained by the mechanisms associated with the mapped copies of IS], IS2, IS3, and IS5 in the region. These features include the discontinuities in homologies between the proA-proC regions of E. coli K-12 and Salmonella typhimurium (3,11,14) and some categories of chromosomal deletions.Recently, a new insertion sequence, IS121 (possibly identical to IS30 [9]), has been reported as a component of the Mu dIl(Ap lac) bacteriophage (12). At least three copies of this 1.2-kb element appear in the chromosomes of several E. coli K-12 strains.…”
mentioning
confidence: 99%
“…There are features of the proA-purE region of the chromosome that are not explained by the mechanisms associated with the mapped copies of IS], IS2, IS3, and IS5 in the region. These features include the discontinuities in homologies between the proA-proC regions of E. coli K-12 and Salmonella typhimurium (3,11,14) and some categories of chromosomal deletions.…”
mentioning
confidence: 99%
See 1 more Smart Citation